2023
DOI: 10.3389/fgene.2023.1098616
|View full text |Cite
|
Sign up to set email alerts
|

The causal association between smoking initiation, alcohol and coffee consumption, and women’s reproductive health: A two-sample Mendelian randomization analysis

Abstract: Objective: A number of epidemiological studies have demonstrated that smoking initiation and alcohol and coffee consumption were closely related to women’s reproductive health. However, there was still insufficient evidence supporting their direct causality effect.Methods: We utilized two-sample Mendelian randomization (TSMR) analysis with summary datasets from genome-wide association study (GWAS) to investigate the causal relationship between smoking initiation, alcohol and coffee consumption, and women’s rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Our study further indicated that nurses who reported coffee or tea consumption were more likely to develop PMS than non-consumers, which also supported previous reports ( 48 ). At present, Existing research supports a link between coffee intake and adverse effects on female hormone levels, including lower estrogen and sex hormone binding globulin (SHBG) ( 50 , 51 ). However, a longitudinal study has yielded opposite results ( 20 ), necessitating further investigation into this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Our study further indicated that nurses who reported coffee or tea consumption were more likely to develop PMS than non-consumers, which also supported previous reports ( 48 ). At present, Existing research supports a link between coffee intake and adverse effects on female hormone levels, including lower estrogen and sex hormone binding globulin (SHBG) ( 50 , 51 ). However, a longitudinal study has yielded opposite results ( 20 ), necessitating further investigation into this relationship.…”
Section: Discussionmentioning
confidence: 99%